2008
DOI: 10.1038/jid.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Processing of Scratching

Abstract: Neuroimaging studies have examined the neural networks activated by pruritus but not its behavioral response, scratching. In this study, we examine the central sensory effects of scratching using blood oxygen level-dependent functional magnetic resonance imaging (fMRI) in 13 healthy human subjects. Subjects underwent functional imaging during scratching of the right lower leg. Scratching stimulus was started 60 seconds after initiation of fMRI acquisition and was cycled between 30-second duration applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 40 publications
8
75
0
2
Order By: Relevance
“…Nevertheless, some data is available on the neurobiology of skin picking, [9,82,96] and there is also a growing literature on the neurobiology of itching and scratching. [97][98][99] Evidence that pharmacotherapy can be effective is consistent with underlying disturbance.…”
Section: Skin Picking Disordermentioning
confidence: 84%
“…Nevertheless, some data is available on the neurobiology of skin picking, [9,82,96] and there is also a growing literature on the neurobiology of itching and scratching. [97][98][99] Evidence that pharmacotherapy can be effective is consistent with underlying disturbance.…”
Section: Skin Picking Disordermentioning
confidence: 84%
“…Coactivation of these regions during itch stimuli implies that the motivational and emotional aspects of itch are also regulated by this network. A recent imaging study of the cerebral processing of scratching suggested that the dorsolateral prefrontal cortex (DLPFC) controls the itch response via possible connections with the amygdala to suppress the itch (Yosipovitch et al 2008). These areas could be targets for drug therapies and psychological biobehavioral treatments for chronic itch.…”
Section: Prefrontal and Limbic Controlmentioning
confidence: 99%
“…En cas de prurit, et contrairement Ă  une situation de douleur, le cortex somato-sensoriel secondaire n'est pas activĂ© spontanĂ©ment, ce qui reprĂ©sente une diffĂ©rence majeure avec la physiologie de la douleur. Il y a une activation importante de cette rĂ©gion et du cortex insulaire, du cortex temporal supĂ©rieur, de l'opercule temporal et mĂȘme du cervelet aprĂšs grattage rĂ©pĂ©titif [31]. Bien que prurit et douleur induisent des rĂ©ponses motrices diffĂ©rentes (grattage dans un cas, retrait ou immobilisation dans l'autre), l'activitĂ© cĂ©rĂ©brale visualisĂ©e par imagerie est la mĂȘme dans les rĂ©gions motrices en cas de prurit ou de douleur.…”
Section: Deux Grandes Voies Relayant La Sensation De Pruritunclassified